2021
DOI: 10.1515/ract-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and behavior of fission product 95Nb in FLiBe salt

Abstract: The 235,238UF4 was irradiated by photo-neutrons, distribution and behavior of the fission product 95Nb from irradiated 235,238UF4 in FLiBe salt were investigated by the measurement of its activity in the salt with the γ-ray spectroscopy. The experiments indicated that a part of 95Nb deposited on the surfaces of graphite and Hastelloy, as the moderator and the structural materials of molten salt reactor (MSR), respectively, and the majority of 95Nb maintained in molten salt. Addition of lithium metal made 95Nb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…In our previous work, 9 it was found that the specic activities of the ssion products 131 I, 140 Ba, 140 La, 141 Ce and 143 Ce remained well a constant during a four-day experimental period. As indicated by ORNL, these nuclides belonged to the salt-seeking ssion products, which dissolved quantitatively and existed steadily in molten salt.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…In our previous work, 9 it was found that the specic activities of the ssion products 131 I, 140 Ba, 140 La, 141 Ce and 143 Ce remained well a constant during a four-day experimental period. As indicated by ORNL, these nuclides belonged to the salt-seeking ssion products, which dissolved quantitatively and existed steadily in molten salt.…”
Section: Resultsmentioning
confidence: 74%
“…Differently from Pa, the deposition of Nb could reach 16% in a similar condition, as reported in our previous work. 9 It was more or less surprising that the specic activity of 233 Pa underwent greater variation compared with those of actinides mentioned above. As shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A self-designed reaction apparatus placed in a glove box in Ar atmosphere was used to investigate the behavior of iodine, and the detailed description has been reported in our previous works. 10,13,14 A graphite crucible with an inner diameter of 25 mm and a height of 60 mm was used as the reaction crucible.…”
Section: Equipmentmentioning
confidence: 99%
“…Thus, their behavior and dependence on the redox potential, especially for 95 Nb, has become one of the key research objects. 9,10 Iodine isotopes are signicant ssion products because of their high yield and wide mass numbers involved in mass distribution. Moreover, they are also the precursor nuclei both for delayed neutron emitters and neutron poison 135 Xe.…”
Section: Introductionmentioning
confidence: 99%